Postnatal lineage mapping of follicular melanocytes with the Tyr:CreERT2 transgene. (20th December 2012) - Harris, Melissa L.; Pavan, William J.
Summary One of the main advantages of using inducible and conditional transgenes to study pigment cell biology is that they allow for genetic manipulation within melanocytes after roles in general neural crest or melanoblast development have been fulfilled. Specifically, we focus here on the ability of the Tyr::CreERT2 transgenic line to alter genes within follicular melanocytes postnatally. Using the Gt(ROSA)26Sortm1sor reporter allele, we present in detail the expression and activity of Tyr::CreERT2 when induced during hair morphogenesis and adult hair cycling. We find that despite similarities in expression pattern to endogenous TYR, Tyr::CreERT2 is effective at targeting both undifferentiated and differentiated melanocytes within the hair follicle. We also find that Tyr::CreERT2 provides the highest levels of recombination when induced during the early phases of hair growth. In conclusion, the descriptions provided here will guide future analyses of gene function within the melanocyte system of the hair follicle when using this Tyr::CreERT2 transgene.